2020
DOI: 10.2147/clep.s269962
|View full text |Cite
|
Sign up to set email alerts
|

<p>Validation of an Algorithm to Ascertain Late Breast Cancer Recurrence Using Danish Medical Registries</p>

Abstract: We constructed an algorithm to ascertain late breast cancer recurrence-which we define as breast cancer that recurs 10 years or more after primary diagnosis (excluding contralateral breast cancers)-using Danish nationwide medical registries. We used clinical information recorded in medical records as a reference standard. Methods: Using the Danish Breast Cancer Group clinical database, we ascertained data on 21,134 women who survived recurrence-free 10 years or more after incident stage I-III breast cancer dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The strengths of this study include the population-based design within a setting of universal tax-supported health care, large sample size, prospective data collection, and long-term and complete follow-up as well as the use of a custom-designed and validated algorithm ( 27 ). Yet, the positive predictive value of our late BCR algorithm was 86% (95% CI = 78% to 91%), so some of our late BCRs could be false positives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strengths of this study include the population-based design within a setting of universal tax-supported health care, large sample size, prospective data collection, and long-term and complete follow-up as well as the use of a custom-designed and validated algorithm ( 27 ). Yet, the positive predictive value of our late BCR algorithm was 86% (95% CI = 78% to 91%), so some of our late BCRs could be false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrences are routinely registered in the DBCG database up to 10 years after diagnosis. We therefore used a previously developed and validated algorithm ( 27 ) to capture patients who developed late BCR using Danish registries. The algorithm incorporated information on diagnostic, therapeutic, and procedural codes from the DNPR and cancer diagnoses from the DCR, DPR, and the database on CBC ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 More information about the 10-year disease-free survivors and the identification of late BC recurrences are available in previous papers. 5,24 Registration of cancer treatments in the DNPR was first mandatory in 2001. 17 We restricted our study population to women who developed recurrent BC from January 1, 2004, and forward.…”
Section: Methodsmentioning
confidence: 99%
“…3 Internationally, algorithms based on routinely collected data like medical claims and cancer-related register data have been developed to identify patients diagnosed with cancer recurrence, mainly from breast and colorectal cancer; the validation of these algorithms has shown mixed results. [6][7][8][9][10][11][12] Recent studies have shown that cancer-specific algorithms based on Danish national health registries can accurately identify patients diagnosed with recurrence of colorectal cancer, 13 breast cancer, [14][15][16] bladder cancer, 17 or endometrial cancer, 18 with little selection bias. However, no similar approach exists to identify patients diagnosed with recurrence of malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%